Assinaturas de Longo Prazo - Pedro Rui Figueiredo da Cunha (2015)
Digital signatures are a requirement for the future. Information in general and documents in particular (the standard being PDF) is increasingly becoming more about bits and bytes and less about paper. But the only way to ensure that this happens successfully is to make a digital signature in all things as equivalent to a traditional one. A signature in itself has undergone major modification throughout the time, from wax seals to hand-written signatures. The next step is digitalization. However, simple digital signatures are not sufficient, since they have a very limited lifespan. This thesis approaches the method of long-term digital signatures in a way that, since there is no definite evaluation between the standards that exist today, there is no clear way to define which one is the best. Hence, one of the goals will be to try and demonstrate in which situation should each one be used and try and make it more definite which one is preferable. Since there is no single or "best" standard, there isn't also a software that can be defined as the one to use where long-term digital signatures are concerned. After a series of tests using the three standards, this dissertation proposes not only a case-by-case use of each standard, but also a software that was developed to aid in the growth of digital signatures as the main method of signing documents and files. The main conclusions are that CAdES is the by-default standard to be used. It is both faster and occupies the least amount of space on disk, which, even though a one for one comparison with XAdES doesn't seem a lot, if we consider thousands of files to be signed, it can reach significant savings. One main disadvantage is that CAdES signatures can't be seen in the file. An mp3 file with a signature will appear as a simple mp3 file. Which is not the case of a XAdES signature, since the output is in XML language. This format can break the functionality of the files, though, if attached to them, hence we save it for XML files, since it made sense to maintain the same formatting scheme of the original file. PAdES is used in one and only one circumstance: to sign PDF files in which the signature is to be included inside the PDF. PAdES uses CAdES as its main signature creation method, but it makes it so that PDF readers that show signatures can display the ones created using PAdES. This is specially important for enterprise use and official documents.